(untitled) (Eurasian Scientific Herald, 2022)
In this article, the author shows the role and importance of the process of solving physical problems in the study of natural phenomena and laws, understanding the physical picture of the world. Also, in order to increase interest in physics, to jointly solve existing physical problems, methods of organizing master classes on modern forms of education were developed, the history of development, their role, goals and objectives in higher education and recommendations on the chosen topic were revealed. It is noted that master classes in physics, which were organized in the past centuries, subsequently led to great discoveries. It was shown that the organization of master classes allows future professionals to work together, learn non-standard thinking, develop creativity and practice their thinking